Dissemination of appropriate technology in the form of Computer Numerically Controlled wood lathes to increase the productivity of the furniture business group in Sekuro Village, Jepara - Solechan Solechan; Rubijanto Juni Pribadi (Community Empowerment, 2022)
The local furniture industry is unable to compete with Chinese products, one of which is a furniture producer in Sekuro Village, Mlonggo District, Jepara Regency, Central Java. The problems faced are relatively high prices, ancient designs, old processes, conventional machines, and low quality of human resources (HR). The purpose of this community service is the dissemination of lathe technology, from conventional to automatic. The community service method is carried out by training on the design of a CNC wood lathe and its use. Productivity is measured based on the feed rate of a CNC wood lathe to surface roughness and processing time. As a result, the highest surface roughness is in the CNC 1 lathe process with a feed rate of 80 m/min 13.24 m. Meanwhile, based on time, CNC wood lathe is more efficient than manual by 37% with a feed rate of 60 m/min for 25:35 minutes. In addition, CNC wood lathe results are more precise, the outer surface is smoother, and the processing time is faster.